2021
DOI: 10.1007/s10792-021-01693-5
|View full text |Cite
|
Sign up to set email alerts
|

Photoablative cosmetic iridoplasty: effective, safe, and predictable—eye color change in 1176 eyes

Abstract: Purpose To evaluate photoablative cosmetic iridoplasty (PCI), and its efficacy, safety, predictability, and satisfaction with the 532 nm Crystal Q-switched Nd: Yag laser, with 3–4 ns pulses, for depigmentation of the anterior epithelium of the iris in cases of heterochromia, nevus, or cosmetic indications (eye color change). Design Prospective clinical study on efficacy, safety, predictability, and satisfaction. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…More recently, a large study of SLT laser (frequency-doubled 532-nm Q-switched Nd:YAG laser in 3–4 ns pulses) on 1176 eyes of 588 human participants has been published. 5 Similar to the previous two studies described, this reported minimal side effects apart from transient iritis. However, although a long-term follow-up schedule was mentioned, only single pre- and post-treatment IOP readings were reported, and it was unclear when the latter measurements took place or whether IOP-lowering therapy was required.…”
Section: Discussionsupporting
confidence: 86%
“…More recently, a large study of SLT laser (frequency-doubled 532-nm Q-switched Nd:YAG laser in 3–4 ns pulses) on 1176 eyes of 588 human participants has been published. 5 Similar to the previous two studies described, this reported minimal side effects apart from transient iritis. However, although a long-term follow-up schedule was mentioned, only single pre- and post-treatment IOP readings were reported, and it was unclear when the latter measurements took place or whether IOP-lowering therapy was required.…”
Section: Discussionsupporting
confidence: 86%
“…During this period, no cases of vision loss were reported. Visual acuity and intraocular pressure also showed no signi cant differences after the treatments (5).…”
Section: Introductionmentioning
confidence: 85%
“…In 2011, we began research to develop a new technique: Photoablative Cosmetic Iridoplasty (PCI) which aimed to treat pigmentary disorders of the iris and achieve purely cosmetic results in a safe and effective manner (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations